Comparison study of water quality in selected disturbed and undisturbed peat swamp forest rivers of Sibu and Bintulu Sarawak - Rosli, Noraini (2012)
A study on status of water quality at natural peat swamp forest and converted peat swamp forest into oil palm plantation was conducted. The peat swamp forest of Batang Igan Sibu and Ladang Semanok Tatau (disturbed peat swamp forest) and Pandan Sebauh Bintulu and Sepadok Bintulu (undisturbed peat swamp forest) were chosen. Peat swamp forest of Batang Igan Sibu and Ladang Semanok Tatau was an oil palm plantation area while Pandan Sebauh Bintulu and Sepadok Bintulu was a natural peat swamp forest. This study was conducted to determine a status of water quality at peat swamp forest of Batang Igan Sibu and other peat swamp forest area for comparative study and to investigate differences between water quality condition in disturbed and undisturbed peat swamp forest. A total of 180 water samples were collected at four different sampling stations (S1, S2, S3 and S4) in six different months from July 2009 to July 2010 at Batang Igan Sibu and once each at Ladang Semanok Tatau, Pandan Sebauh Bintulu and Sepadok Bintulu within December 2010 to April 2011. In-situ data included temperature; conductivity, dissolved oxygen (DO), pH and turbidity were recorded. Ammoniacal nitrogen (NH3-N), biochemical oxygen demand (BOD), chemical oxygen demand (COD) and total suspended solids (TSS) were conducted in the laboratory. The Water Quality Index (WQI) which was calculated based on six water quality parameters namely dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, pH, ammoniacal nitrogen and total suspended solids, was representative of the state of water quality at study area. Results for water quality parameters shows, temperature range (29.4-30.31°C), pH range (3.66- 4.1), DO range (3.37-3.86 mg/L), conductivity (69.67-80.73 μS cm-1), TSS range (25-27.7 mg/L), turbidity (4.15-5.2 NTU), BOD range (3.55-3.6 mg/L), COD (30-38 mg/L) and ammoniacal nitrogen (0.38-0.41 mg/L) at river water of Batang Igan Sibu and Ladang Semanok Tatau. This study showed that the physical-chemical parameters of water in peat swamp forest of Batang Igan Sibu and Ladang Semanok Tatau were range from Class II, Class III and Class IV respectively. The most influence parameter that causes the deteriorating of water quality to Class III is DO, BOD, COD and ammonia analysis and Class IV for pH. pH and dissolved oxygen of the water were found under very poor water quality status; however it is normal for peat water. Based on WQI of river water at peat swamp forest at Batang Igan Sibu and Ladang Semanok Tatau, S1, S2, S3 and S4 were categorized under Class III (moderate water quality) while river water at Pandan Sebauh Bintulu and Sepadok Bintulu categorized under Class II (good water quality). The physical-chemical parameters of water at Pandan Sebauh Bintulu and Sepadok Bintulu were range from Class I and Class II; except for DO of water that is categorized under Class III and Class IV for pH. This study showed that the river water of peat swamp forest at Batang Igan Sibu and Ladang Semanok Bintulu (disturbed peat swamp forest) was affected due to agricultural and oil palm plantation activities that took place at that area while compared to river water at peat swamp forest of Pandan Sebauh Bintulu and Sepadok Bintulu (undisturbed) were under Class II (good water quality).